176k views
0 votes
Solve the equation:5(3+6a)=-15+6(5+5a)

User BoxerBucks
by
4.8k points

1 Answer

0 votes

Answer:

0.5

Explanation:

To solve the equation 5(3+6a) = -15+6(5+5a), we need to use the rules of algebra to isolate the variable "a" on one side of the equation and simplify the other side.

First, we can distribute the 5 on the left side of the equation to obtain 53 + 56a = -15+6(5+5a). This gives us 15 + 30a = -15+6(5+5a).

Next, we can distribute the 6 on the right side of the equation to obtain 15 + 30a = -15+65 + 65a. This gives us 15 + 30a = -15+30 + 30a.

Now we can combine like terms on both sides of the equation to obtain 30a = -15 + 30, which simplifies to 30a = 15. Finally, we can divide both sides of the equation by 30 to obtain a = 0.5.

Therefore, the solution to the equation 5(3+6a) = -15+6(5+5a) is a = 0.5

User Lochlan
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.